Role Person Old and Teacher in Guidance Counseling for Talent Children in School Base - Hunaina, Najma; Septian, Rudi; Nurkhotimah, Uliyana; Fitriyani, Fitriyani (International Journal Of Education, Social Studies, And Management (IJESSM), 2024)
This research documents the implementation of guidance and counseling services at the Bekasi Jaya Special School (SLBN), Indonesia, in the context of inclusive education. Inclusive education provides equal opportunities for Children with Special Needs (ABK), in accordance with the Minister of National Education Regulation No. 70 year 2009. With method study qualitative, study This focus on the role of consultation, improvement, and communication in guidance and counseling services. Consultations serve as an urgent response to emerging problems, allowing for quick and tailored solutions to student needs. Improvements focused on infrastructure constraints to create an optimal learning environment. Intensive communication with parents is a key element to involve them in their children's education. This service reflects implementation principle democracy education, in where every child recognized have equal rights to quality education. The conclusions of this study support the theory of inclusive education which emphasizes response to the unique needs of each student. Guidance and counseling services at SLBN Bekasi Jaya are not only a response to problems, but also a proactive strategy for optimal learning success. This conclusion provides an in-depth understanding of the implementation of inclusive education at the special school level, with a focus on consultation, improvement and communication as integral elements.